Strategic decision processes among senior executives of SEDC companies: a cognitive diversity perspective / Abdullah Abdul Ghani … [et al.] - Abdul Ghani, Abdullah; Mohd. Mokhtar, Sany Sanuri; Ramli, Azahari; Ashari, Hasbullah (Institute of Quality & Knowledge Advancement (InQKA), 2005)
In earlier studies involving business organizations in the American free enterprise economy, cognitive diversity among upper-echelon executives was found to inhibit strategic decision processes. Taking cognizance of the consistent results of previous studies about the significant impact of environment on decision processes, we replicated the study by Miller, Burke and Glick (1998) on Malaysia's State Economic Development Corporations - business entities currently operating in controlled and favored environment. It was a cross-sectional study of the descriptive and correlational type involving a total sample size of 130 executives and a participation rate of 53.07% based on proportion of the total number of questionnaire that was duly completed and returned. Our results found that contrary to expectation, cognitive diversity among executives did vary among the various SEDC and such diversity promoted rather than inhibited strategic decision making processes. Since cumulative research findings showed that firm performance was related to both comprehensiveness and extensiveness of the decision making process, our results, like that of the original study, provided another evidence of indirect executive diversity-firm performance relationship. Indeed, we had observed in this study indications that SEDC with high cognitive diversity among their decision-making executives tend to show better financial performance than those with lower cognitive diversity.